Arterial hypertension and lifestyle of waterway workers - Jorge Luiz Lima da Silva; Jonathan Henrique Anjos de Almeida; Rafael da Silva Soares; Monyque Evelyn dos Santos Silva; Enéas Rangel Teixeira; Jones Alberto de Almeida (Rev Rene)
Objective: to describe the prevalence of arterial hypertension among workers of water transportation company in the state of Rio de Janeiro. Methods: it is a sectional study performed with 316 employees. Socio-demographic variables, labor, of lifestyle and health were analyzed; the numbers above 120/80 mmHg were considered as an initial risk for hypertension. Results: the prevalence of hypertension (>140/90mmHg) was 19.3%. The prevalence of blood pressure values above 120/80mmHg was 65.5%. Male gender (p=0.001); age over 35 years (p=0.014); marital status (p=0.040); presence of children (p=0.013); permanent job (p=0.015); be more than five years in the industry (p=0.004), high body mass index (p=0.001) and the unawareness of having high pressure (p=0.001) were associated with hypertension. Conclusion:the findings contribute to the knowledge of health area of workers and provide subsidies to nursing, can perform planning activities and multidisciplinary interventions.